The major histocompatibility complex homozygous inbred Babraham pig as a resource for veterinary and translational medicine - Schwartz, J.C.; Hemmink, J.D.; Graham, S.P.; Tchilian, E.; Charleston, B.; Hammer, S.E.; Ho, C.S.; Hammond, John A. (Wiley, 2018)
The Babraham pig is a highly inbred breed first developed in the United Kingdom approximately 50 years ago. Previous reports indicate a very high degree of homozygosity across the genome, including the major histocompatibility complex (MHC) region, but confirmation of homozygosity at the specific MHC loci was lacking. Using both direct sequencing and PCR‐based sequence‐specific typing, we confirm that Babraham pigs are essentially homozygous at their MHC loci and formalise their MHC haplotype as Hp‐55.6. This enhances the utility of the Babraham pig as a useful biomedical model for studies in which controlling for genetic variation is important.